The Teutonic Order in Italy, 1190-1525: building bridges in the medieval world - Toomaspoeg, Kristjan (The military religious orders: history, sources, and memory, 2024)
Between 1190 and 1525, the Teutonic Order maintained extensive possessions in Italy